A framework for benchmarking competency assessment models. Issue 1 (23rd August 2012) - Kasser, Joseph; Hitchins, Derek; Frank, Moti; Zhao, Yang Yang
Abstract This paper discusses the need for competent systems engineers, the differences between nine current ways of assessing competencies (competency models) and the difficulty of comparing the competency models due to the different ways each model groups the competencies. The paper then introduces a competency model maturity framework (CMMF) for benchmarking competency models of systems engineers. The paper benchmarks the nine models using the CMMF and a surprising finding was an error of omission in all nine models. The paper shows that the CMMF can also be used as the basis for developing an original model for a specific organization in a specific time and place and concludes with suggestions for future research. ©2012 Wiley Periodicals, Inc. Syst Eng 15